Synthesis of poly-3-hydroxyalkanoates is a common feature of fluorescent pseudomonads. - Huisman, G W (1989)
The fluorescent pseudomonads are classified as a group, one characteristic of which is that they do not accumulate poly-3-hydroxybutyrate (PHB) during nutrient starvation in the presence of excess carbon source. In this paper we show that prototype strains from this subclass, such as Pseudomonas aeruginosa, Pseudomonas putida, and Pseudomonas fluorescens, do accumulate poly-3-hydroxyalkanoates (PHA) when grown on fatty acids. These PHAs are composed of medium-chain-length (C6 to C12) 3-hydroxy fatty acids. The ability to form these polyesters does not depend on the presence of plasmids. A specificity profile of the enzymes involved in the biosynthesis of PHA was determined by growing Pseudomonas oleovorans on fatty acids ranging from C4 to C18. In all cases, PHAs were formed which contained C6 to C12 3-hydroxy fatty acids, with a strong preference for 3-hydroxyoctanoate when Ceven fatty acids were supplied and 3-hydroxynonanoate when Codd fatty acids were the substrate. These results indicate that the formation of PHAs depends on a specific enzyme system which is distinct from that responsible for the synthesis of PHB. While the fluorescent pseudomonads are characterized by their inability to make PHB, they appear to share the capacity to produce PHAs. This characteristic may be helpful in classifying pseudomonads. It may also be useful in the optimization of PHA production for biopolymer applications.